Comparison of the Effects of Haloperidol, Metoclopramide, Dexmedetomidine and Ginger on Postoperative Nausea and Vomiting After Laparoscopic Cholecystectomy - Naemi, Amir Reza (J Med Life, 2020)
Nausea is a mental sensation of unease and discomfort before vomiting. Vomiting refers to the return of the contents of the upper gastrointestinal tract to the mouth caused by contractions of chest and abdomen muscles. Postoperative nausea and vomiting is an unpleasant experience with high treatment costs. Therefore, this study aimed to compare the effects of haloperidol, metoclopramide, dexmedetomidine, and ginger on postoperative nausea and vomiting after laparoscopy. This double-blind clinical trial was performed on all laparoscopy candidates at Valiasr hospital, Arak, Iran. The patients were randomly divided into four groups (haloperidol, metoclopramide, dexmedetomidine and ginger), and all patients underwent general anesthesia using fentanyl, midazolam, atracurium, and propofol. After intubation, tube fixation, and stable hemodynamic conditions, the patients received four ginger capsules with a hint of lemon. A group of patients received 25 μg of dexmedetomidine. In the Plasil group, 10 mg of metoclopramide was given 30 minutes before the completion of surgery. In addition, 0.5 cc of haloperidol (5 mg) was administered to a group of patients. Heart rate, blood pressure, and oxygen saturation were recorded from the beginning of surgery, every 15 minutes until the end of the surgery. Furthermore, the occurrence of nausea and vomiting was recorded during recovery, 2 and 4 hours after surgery. Data were then analyzed using the SPSS software v.23. Eighty-eight patients were enrolled in the study. The youngest and the oldest were 30 years and 70 years old, respectively, and the mean age was 48.02 ± 9.31 years. Moreover, the number of women in the four groups was higher than that of men. Blood pressure in the dexmedetomidine group was lower than the other four groups (P <0.05). The lowest heart rate was observed in the haloperidol group, while the highest heart rate was seen in the plasil group (P <0.05). The occurrence of vomiting and nausea was not significantly different between the four groups (P <0.05). Our results showed no significant difference in postoperative nausea and vomiting between the four drugs. Due to the hemodynamic changes induced by each drug, it is best to use these drugs based on the patient’s condition. Ginger is also a herbal remedy that has fewer side effects, and this drug can be a good option for patients when there is no contraindication.